SAR flexible antenna advancements: Highly conductive polymer-graphene oxide-silver nanocomposites - Al Gburi, Ahmed Jamal Abdullah; Ismail, Mohd Muzafar; Mohammed, Naba J.; Alghamdi, Thamer A. H. (Electromagnetics Academy, 2024)
In the past, copper served as the material for conductive patches in antennas; however, its usage was constrained due to high costs, susceptibility to fading, bulkiness, environmental sensitivity, and manufacturing challenges. The emergence of graphene nanotechnology has positioned graphene as a viable alternative, offering exceptional electrical conductivity, strength, and adaptability. In this study, graphene is employed to fabricate conductive silver nanocomposites. The silver-graphene (Ag/GO) sample exhibits an electrical conductivity of approximately 21.386 S/cm−1 as determined by the four-point probe method. The proposed flexible antenna, characterized by four carefully selected cylindrical shapes, is used to construct the antenna patch for enhanced bandwidth and resonates at 2.47 GHz. It achieves remarkable performance characteristics, with a high gain of 11.78 dBi and a return loss greater than −20 dB. Safety considerations are addressed by evaluating the Specific Absorption Rate (SAR). For an input power of 0.5 W, the SAR is calculated to be 1.2 W/kg per 10 g of tissue, affirming the safety of integrating the suggested graphene flexible antenna into flexible devices. In this study, the bending of the antenna was assessed by subjecting the structure to bending at various radii and angles along both the X and Y axes. These findings underscore the promising utility of Ag/GO nanocomposites in the development of flexible antennas for wireless systems.